IoT-based guppy fish farming monitoring and controlling system - Periyadi Periyadi; Gita Indah Hapsari; Zahir Wakid; Sobran Mudopar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Nowadays, monitoring of guppy fish farming is still done manually. A monitoring and control system is needed to make it easier for guppy fish farmers. This system consists of a sensor module and monitoring module. Sensor module detects the value of pH and salinity of water and send it to the monitoring module. Monitoring is used as a web-based system using IoT technology. This web-based system serves to monitor and control the pH value and only monitor the salinity value. The workings of the monitoring and control system send data on pH and salinity sent by the sensor and then stored and in database hosting. Data on the database will be displayed on the website using wireless media, making it easier for users to view data and information remotely. Beside, farmers are facilitated in knowing the value of pH and salt content dissolved in water. For the value of a dangerous salt content worth less than 160 and more than 210, if for a pH of less than 6.5 and more than 7.5. Farmers are also facilitated to control pH with servo motors through the website, so farmers can prevent if the pH content dissolved in water is dangerous for guppy fish.